Comparing fourth-year medical students’ procedural surgical skill learning outcomes between third-person point-of-view video lectures and first-person point-of-view immersive virtual reality: a pilot study of surgically implanting a subdermal drain on cadavers - Neuwirth, Lorenz S.; Ng, Sam; Devors, Sandrine; Lonjon, Nicolas; Ros, Maxime (Frontiers in Virtual Reality, 2024)
The use of virtual reality (VR) training in medical school education has increased over the last decade partly due to the coronavirus-19 and also due to technology advancements in this integrative area. As medical students are being trained in new pedagogical interventions, it is important to drill-down and focus on the areas of most translational concern for assessing competency and proficiency. Thus, the present pilot study sought to evaluate a group of fourth-year medical students ability to learn a modified medical school curriculum on implementing a subdermal drain by first learning how to stitch on a silicone model (i.e., proper stitching only) and then being randomly assigned to either a Third-Person Point-of-view (TP-POV) or First-Person Point-of-view (FP-POV) immersive VR group to learn how to conduct the surgical procedure (i.e., conceptually and procedurally). Then the participants surgical procedural motor skills were assessed on a single attempt to demonstrate their competency and proficiency on a cadaver. The results showed that the pedagogical learning differences in FP-POV immersive VR improved the cleanliness and accuracy of the surgical dissection movement and drain placement with 100% proficiency in a first-attempt at implementing this surgical technique on a cadaver. Additionally, there was statistically significant improvement in the Dissection movement (p < 0.05*) and the Tension test (p < 0.01**) in the FP-POV group compared to the TP-POV group, even with a small sample size in the present pilot study. These findings offer unique training opportunities to be considered when designing future VR curriculum with the suggested use of repeated-measures designs on the surgical procedural motor skills to assess learning curves and its potential translations in reducing operating room errors, costs, planning and scheduling times, and surgery overlaps; thereby, positively contributing to a more efficient and safer OR surgical experience by staff and patients in the near future.